2012
DOI: 10.1158/0008-5472.can-11-4106
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 Phosphorylation Defines ABT-737 Resistance That Can Be Overcome by Increased NOXA Expression in Leukemic B cells

Abstract: ABT-737 is a small molecule Bcl-2 homology (BH)-3 domain mimetic that binds to the Bcl-2 family proteins Bcl-2 and Bcl-xL and is currently under investigation in the clinic. In this study, we investigated potential mechanisms of resistance to ABT-737 in leukemia cell lines. Compared with parental cells, cells that have developed acquired resistance to ABT-737 showed increased expression of Mcl-1 in addition to post-translational modifications that facilitated both Mcl-1 stabilization and its interaction with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(120 citation statements)
references
References 46 publications
(65 reference statements)
4
109
1
Order By: Relevance
“…However, this report did not identify molecular changes underlying the abnormal expression. Konopleva et al and Mazumder et al 46,47 reported that phosphorylation of BCL2 or increased levels of MCL1 impeded ABT-737-induced apoptosis in cancer cells, which could be restored upon inhibition of BCL2 phosphorylation and reduction of MCL1 expression. Again, these manuscripts did not report mutations in BCL2-family proteins associated with ABT-737 resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, this report did not identify molecular changes underlying the abnormal expression. Konopleva et al and Mazumder et al 46,47 reported that phosphorylation of BCL2 or increased levels of MCL1 impeded ABT-737-induced apoptosis in cancer cells, which could be restored upon inhibition of BCL2 phosphorylation and reduction of MCL1 expression. Again, these manuscripts did not report mutations in BCL2-family proteins associated with ABT-737 resistance.…”
Section: Discussionmentioning
confidence: 99%
“…26 MCL-1/BIM complex, and then the freed BIM induces apoptosis through BAX activation. 27 Other therapeutics, including proteasome inhibitors, may act similarly by activating the endoplasmic reticulum-specific transcription factors ATF3 and ATF4 that regulate NOXA expression. 28,29 Determining the dependence on a particular antiapoptotic BCL-2 family protein has become critical for deciding a personalized therapy.…”
Section: Development Of Bh3 Mimetic Drugsmentioning
confidence: 99%
“…24 The emergence of Bcl-2 inhibitors such as ABT-263 and ABT-199 are showing considerable promise for the treatment of CLL, however these drugs are unable to inhibit the antiapoptotic effects of Mcl-1 conferred by the microenvironment, 25 thus identifying a known mechanism of resistance to these BH3-mimetics. [26][27][28][29] Several pan-Bcl-2 family inhibitors such as obatoclax, sabutoclax and AT-101 have been developed with low micromolar potency against Mcl-1. Obatoclax (a BH-3 mimetic) has been investigated in a phase I clinical trial for advanced CLL, but its effect was limited.…”
Section: Introductionmentioning
confidence: 99%